Research on energy consumption monitoring and control method of energy saving and emission reduction for hybrid ships. Issue 1 (March 2021) - Li, Fangxuan
Abstract: Hybrid ship as a kind of transport mode with high energy consumption, the monitoring of energy consumption and the control of energy conservation and emission reduction are particularly important. Therefore, effective energy consumption monitoring and emission control methods in the process of ship operation have attracted great attention in related fields. Therefore, this study optimized the structure of the energy consumption monitoring equipment for hybrid ships, and achieved the energy consumption monitoring and control by effectively collecting the energy consumption data of hybrid ships. The application of real-time monitoring system for ship energy consumption can better monitor the energy consumption of hybrid ships and realize the treatment and control of energy conservation and emission reduction according to the monitoring results. At the same time, according to the current situation of ship energy consumption management, through the analysis of the characteristics of ship operation and diesel engine fuel system, this study proposed a low loss, high precision mass flowmeter, to achieve the requirements of energy conservation and emission reduction control. Based on this, strengthening ship basic management, saving Marine fuel and reducing pollution can achieve a win-win situation between economy and environment.